Gasing Game: Ethnoscientific Exploration of Circular Motion in Physics Learning on the Coast of East Sumatra to Build the Character of Perseverance - Jusmaniar Jusmaniar; Imelda Riani; Eric C Anderson; Mei Chi Lee; Sri Wina Oktavia (Schrödinger: Journal of Physics Education, 2024)
Purpose of the study: The aim of this research is to explore the role of the traditional gasing game as a local wisdom in the coastal areas of East Sumatra in the context of Ethnoscience Physics learning about circular motion. Methodology: This research uses a naturalistic type of qualitative research method. The subjects in this research were secondary school physics teachers and local community leaders. Data collection techniques use interviews and observation instruments (direct observation). The data analysis technique uses the Miles and Huberman model. Main Findings: The findings of this research indicate that integrated ethnoscientific physics learning can make physics education more enjoyable, meaningful, and contribute to the development of students' perseverance. The integration of spinning top games into physics education not only enhances practical understanding of physics concepts but also has a positive impact on students' learning enthusiasm and character formation. Novelty/Originality of this study: This research introduces novelty through serving as a cultural preservation tool for the younger generation and as a means to develop physics learning strategies oriented towards ethnoscientific physics. The aim is to build an understanding of the taught circular motion material and foster perseverance in students' characters.